Impact of training and experience in using ICT on in-service teachers' basic ICT literacy - Mahmud, Rosnaini; Ismail, Mohd Arif (Malaysian Educational Technology Association, 2010)
The aim of this paper is to report on a study that explored the impact of ICT training and ICT experience on teachers’ basic ICT literacy in terms of ICT knowledge, skills and attitude. The study employed a quantitative approach in the form of a survey. A total of 303 teachers were randomly selected as research samples. Data were gathered through a set of instruments consisting of an ICT attitude questionnaire, and ICT knowledge and skills tests. Data were analyzed descriptively and inferentially using mean, percentage, frequency and multivariate analysis of variance (MANOVA). Findings demonstrated that majority of the teachers had moderate basic ICT knowledge and skills, and perceived ICT positively. Formal ICT training and experience in using ICT were found to influence and contribute to teachers’ ICT literacy significantly.